Pengaruh Model Pembelajaran PjBL Terintegrasi Etnosains Terhadap Hasil Belajar Mahasiswa - Lumbangaol, Sudirman T.P.; Simanullang, Ady Frenly; Sijabat, Apriani (PendIPA Journal of Science Education, 2024)
This research aimed to analyze the influence of the Project-Based Learning (PjBL) learning model integrated with ethnoscience on student learning outcomes. The method used was a quasi-experiment with a pretest-posttest control group design. The research sample consisted of two classes of students taken randomly, where one class used the ethnoscience integrated PjBL model and the other class applied conventional learning methods. Data was collected through learning outcomes tests and analyzed using the t test to determine significant differences between the two groups. The research results show that the application of the ethnoscience integrated PjBL model provides a significant improvement in student learning outcomes compared to conventional methods. This research concludes that the integration of ethnoscience in PjBL learning can increase students' understanding and involvement, and encourage them to relate lesson material to the local cultural context.